Demise Life - Davis, Marcy (Stimulus: A Medical Humanities Journal, 2023)
Demise Life is a glass- blown sculpture with cold worked designs and is an investigation of the loss of the beginning of life. This sculpture reflects the loss of human connection and the grief that encompasses it. As light passes through this sculpture, the shadows metamporph the space into a place of rememberance of the demised life.